Time–frequency causality between stock prices and exchange rates: Further evidences from cointegration and wavelet analysis - Afshan, Sahar; Sharif, Arshian; Loganathan, Nanthakumar; Jammazi, Rania (Elsevier B.V., 2018)
The current study investigates the relationship between stock prices and exchange rate by using wavelets approach and more focused the continuous, power spectrum, cross and coherence wavelet.The result of Bayer and Hanck (2013) and Gregory and Hansen (1996) confirm the presence of long-run association between stock price and exchange rate in Pakistan.The results of wavelet coherence reveal the dominance of SP during 2005–2006 and 2011–2012 in the period of 8–16 and 16–32 weeks cycle in approximately all the exchange rates against Pakistani rupees.For almost the entire studied period in long scale, the study evidences the strong coherence between both the series.The most interesting part of this coherence is the existence of bidirectional causality in the long timescale.The arrows in this long region are pointing both left up and left down.This suggests that during the time period, our variables are exhibiting out phase relationship with mutually leading and lagging the market. These results are in contrast with many earlier studies of Pakistan.